Comparação de métodos de tratamento de amostras de biodiesel para determinação de Sódio usando espectrometria de absorção atômica com chama - Leonardo, Ana Cristina de Almeida (2016)
Most analytical methods require a sample preparation to make it compatible with the technique and the equipment used. This paper proposes a comparison between alkaline solubilization using TMAH 25% and acid extraction with heating using HNO3 0.1 mol L -1 as preparation of biodiesel samples in order to determine sodium. The analytical technique used in this study was Flame Atomic Absorption Spectrometry - FAAS. The biodiesel samples used were synthesized from three commercially available oils: babassu oil, corn and soybeans. The interlaboratory biodiesel sample used to compare the proposed method with the official NBR 15556:2008, was provided by Laboratory of Analysis and Research in Analytical Chemistry of Petroleum and Biofuels - LAPQAP/UFMA. The final solution after solubilization with 25% TMAH in methanol was incompatible with FAAS technique. The high viscosity of the sample influenced directly in the aspiration causing significant variations in the readings and making it impossible to continue the analysis. Acid extraction HNO3 0.1mol.L -1 yielded better results, in addition, the physical conditions of the final solution were consistent with FAAS. The LOD and LOQ values were respectively 0.02 and 0.07 mg.Kg-1 for sodium. The obtained recoveries were between 102 and 110% at three different levels of fortification. In comparison with the dilution of biodiesel in xylene established by official standards, quantified concentrations showed values very close. The simplicity, accuracy, precision, less toxicity and low cost of the acidic extraction method suggest that this may be a good alternative for treating biodiesel sample to determine sodium.